Trends in socioeconomic inequalities in child undernutrition: Evidence from Nigeria Demographic and Health Survey (2003 - 2013). - Blessing J Akombi; Kingsley E Agho; Andre M Renzaho; John J Hall; Dafna R Merom (PLoS ONE, 2019)
Objective The aim of this study was to examine the trend in socioeconomic inequalities in child undernutrition in Nigeria. Methods The study analysed cross-sectional data from the Nigeria Demographic and Health Survey (NDHS) 2003 to 2013. The outcome variables were stunting, wasting and underweight among children under-five years. The magnitude of child undernutrition in Nigeria was estimated via a concentration index, and the socioeconomic factors contributing to child undernutrition over time were determined using the decomposition method. Results The concentration index showed an increase in childhood wasting and underweight in Nigeria over time. The socioeconomic factors contributing to the increase in child undernutrition were: child's age (0-23 months), maternal education (no education), household wealth index (poorest household), type of residence (rural) and geopolitical zone (North East, North West). Conclusions To address child undernutrition, there is a need to improve maternal education and adopt effective social protection policies especially in rural communities in Nigeria.